Maternal antepartum antibiotic administration and patterns of bacterial resistance in early preterm neonates. (18th April 2022) - Romagano, Matthew P.; Fofah, Onajovwe; Swaminarayan, Dhaval; Williams, Shauna; Apuzzio, Joseph J.; Gittens-Williams, Lisa
Abstract: Objective: The objective of this study was to determine the relationship between maternal antepartum antibiotic administration and antibiotic resistance patterns in preterm neonates admitted to the neonatal intensive care unit (NICU). Methods: This was a retrospective cohort study of women and their preterm neonates delivered at a single tertiary care center over a 5-year period. Women and neonates were included if they delivered between 23 weeks 0 days and 28 weeks 6 days of gestation and neonates were admitted to the NICU. Subjects were excluded if there was incomplete antibiotic administration data or incomplete laboratory or bacterial culture data for either mothers or neonates. Data collected from maternal and neonatal charts included the type, duration, and total number of antibiotics administered to subjects, neonatal culture results within the first 7 days of life, and bacterial antibiotic resistance information. Women with neonates that cultured positive for bacteria demonstrating antibiotic resistance were compared to those whose neonates did not have antibiotic-resistant bacteria. Results: 79 women with 90 neonates met inclusion criteria. Of the 79 women, 71 (89.9%) received at least 1 antibiotic antepartum. 14 neonatal bacterial isolates were resistant to at least 1 antibiotic. Antibiotic-resistant bacteria were present in 11 neonates; 3 neonates had more than 1 resistant bacteria cultured. The most common resistant bacteria cultured were Coagulase-negative Staphylococcus (6/14, 42.9%), S. aureus (3/14, 21.4%), and E. coli (2/14, 14.3%). Enterobacter spp (2) and Klebsiella pneumoniae (1) made up the remainder. Of the 11 neonates with resistant bacteria isolated, 10 of their mothers received antibiotics antepartum. Neonates with antibiotic-resistant bacterial isolates were more likely to be born at lower gestational ages (24.6 vs 25.9 weeks, p  = .013) and have lower mean birth weights (679.5 vs 849.3 g, p  = .009) than those without resistant bacteria. In 8 of 11 (73%) neonates with resistant bacteria, the mother received an antibiotic to which the bacteria cultured were resistant: 6 coagulase-negative Staphylococcus, 1 MRSA, and 1 S. aureus. Conclusions: Although preterm neonates are often treated for presumed sepsis, they infrequently have positive bacterial cultures. In this study, those that had positive bacterial cultures for resistant bacteria were born at earlier gestational ages and had lower birth weights. These bacteria cultured in neonates are likely to be resistant to antibiotics received by mothers in the antepartum period. Careful selection of maternal and neonatal antibiotics in the preterm setting with consideration for local antibiotic resistance patterns is suggested.